2020
DOI: 10.1136/bmjopen-2020-037080
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and risk of cardiovascular diseases: a Danish population-based matched cohort study

Abstract: ObjectivesTo assess the risks of myocardial infarction, stroke, peripheral artery disease, venous thromboembolism, atrial fibrillation or atrial flutter and heart failure in patients with constipation compared with a general population cohort.DesignPopulation-based matched cohort study.SettingAll Danish hospitals and hospital outpatient clinics from 2004 to 2013.ParticipantsPatients with a constipation diagnosis matched on age, sex and calendar year to 10 individuals without constipation from the general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
1
32
0
2
Order By: Relevance
“…13 A large population-based cohort study revealed that constipation was associated with an increased risk of HF. 14 Therefore, it is important to manage and prevent constipation in HF patients.…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…13 A large population-based cohort study revealed that constipation was associated with an increased risk of HF. 14 Therefore, it is important to manage and prevent constipation in HF patients.…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Крупное популяционное когортное исследование с участием более 83 тыс. пациентов после поправок на коморбидность и лекарственную терапию продемонстрировало ассоциации хронического запора с венозными тромбоэмболическими осложнениями (ОР 2,04), инфарктом миокарда (ОР 1,24), ишемическим (ОР 1,50) и геморрагическим инсультами (ОР 1,46), а также заболеваниями периферических артерий (ОР 1,34), фибрилляцией/ трепетанием предсердий (ОР 1,27) и сердечной недостаточностью (ОР 1,52) [12]. В национальном когортном исследовании с участием 237 тыс.…”
Section: запор как фактор риска неблагоприятных исходов у лиц старшего возрастаunclassified
“… 14 A previous study found constipation was associated with the increased risk of HF. 15 However, it is unclear about the contribution of constipation and dietary patterns to the prognosis of HF.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is associated with age, diabetes mellitus, hypertension and a lack of exercise, which are risk factors for CVD 14. A previous study found constipation was associated with the increased risk of HF 15. However, it is unclear about the contribution of constipation and dietary patterns to the prognosis of HF.…”
Section: Introductionmentioning
confidence: 99%